Changes in serum amylase and its isoenzymes after whole body irradiation. Issue 6336 (17th July 1982) - Barrett, A; Jacobs, A; Kohn, J; Raymond, J; Powles, R L
Abstract : A study was carried out to assess the effect of total body irradiation on pancreatic and parotid isoenzymes of amylase in patients about to undergo bone-marrow transplantation who had received high-dose cyclophosphamide. Twelve patients were studied, enzyme activity being measured before and at various times after total body irradiation. Serum total amylase activity rose rapidly within 12 hours of irradiation to a maximum at 36 hours, returning to normal by six days; most of the increase was derived from salivary damage, with a much smaller pancreatic component. These results confirm that radiation produces acute changes in amylase activity, which may be of use in assessing radiation-induced damage.